1968
DOI: 10.3181/00379727-127-32809
|View full text |Cite
|
Sign up to set email alerts
|

Herpes-Type Virus Recovery from "Virus-Free" Frog Kidney Tumors

Abstract: Spontaneous renal adenocarcinomas of Rana pipiens exist in two seasonal forms within the same populations of northern United States frogs. Tumors from animals collected in winter monlths display negligible mitotic activity and contain numerous cells characterized by enlarged nuclei with marginated chromatin and Cowdry (1) type A inclusions. A constant association of herpes-type virus with inclusion-conltaining cells has been demonstrated by electron microscopic studies of these naturally occurring winter tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Rafferty (1965) showed that intranuclear inclusions developed in tumours which were free of such inclusions several months after the environment of the host frogs was changed to a temperature of 4°C. Similar results were obtained by Mizell, Stackpole, and Halperen (1968), and this latter group extended their study to show that virus particles as well as inclusions appeared in tumours, previously free of particles and inclusions, which had been transferred to the anterior chamber of the eye of Rana pipiens and other species of frog and subsequently kept at 7 5°C (Mizell et al, 1968;Mizell, Stackpole, and Isaacs, 1969). More recently organ cultures of tumours without inclusions have been shown to develop inclusions when the cultures were held at 9°C (Morek and Tweedell, see Granoff, 1972).…”
Section: Herpesvirus Of Lucke Renal Carcinoma Of North American Leopasupporting
confidence: 90%
“…Rafferty (1965) showed that intranuclear inclusions developed in tumours which were free of such inclusions several months after the environment of the host frogs was changed to a temperature of 4°C. Similar results were obtained by Mizell, Stackpole, and Halperen (1968), and this latter group extended their study to show that virus particles as well as inclusions appeared in tumours, previously free of particles and inclusions, which had been transferred to the anterior chamber of the eye of Rana pipiens and other species of frog and subsequently kept at 7 5°C (Mizell et al, 1968;Mizell, Stackpole, and Isaacs, 1969). More recently organ cultures of tumours without inclusions have been shown to develop inclusions when the cultures were held at 9°C (Morek and Tweedell, see Granoff, 1972).…”
Section: Herpesvirus Of Lucke Renal Carcinoma Of North American Leopasupporting
confidence: 90%
“…These were present both in the nucleus and in the cytoplasm, always associated with inclusion bodies, and were found only in frogs that had been captured during winter. Temperature sensitivity of the virus has been demonstrated by transplantation of summer tumor fragments in the anterior chamber of the eye of leopard frogs known not to carry the virus and maintaining them at a temperature of 7 .5°C, whereupon virus particles developed in the tumor implants (Mizell et al, 1968. The activation of previously latent virus in summer tumor tissue has also been accomplished in vitro with tumor fragments incubated at 7 .5°C on agar slants (Breidenbach etal., 1971).…”
Section: Renal Adenocarcinoma In the Frogmentioning
confidence: 97%
“…Prolonged low temperatures favored the production of both; thus, tumors from frogs captured in the winter and spring more frequently contained inclusions and virus particles. If frogs bearing primary virus-free tumors were kept for prolonged periods at low temperatures, the herpesvirus particles appeared in the tumor cells (44). Granoff and his co-workers isolated a virus, FV-l, from the frog tumor cells which was unable to replicate at 33°C although replication occurred at 24°C (45).…”
Section: Herpesvirusesmentioning
confidence: 99%